2015
DOI: 10.1186/s13012-016-0458-7
|View full text |Cite
|
Sign up to set email alerts
|

External facilitators and interprofessional facilitation teams: a qualitative study of their roles in supporting practice change

Abstract: BackgroundFacilitation is a powerful approach to support practice change. The purpose of this study is to better understand the facilitation roles exercised by both external facilitators and interprofessional facilitation teams to foster the implementation of change. Building on Dogherty et al.’s taxonomy of facilitation activities, this study uses an organizational development lens to identify and analyze facilitation roles. It includes a concise definition of what interprofessional facilitation teams actuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 49 publications
6
89
0
Order By: Relevance
“…ORIGINAL ARTICLES I n health care literature, the term "practice facilitator" describes someone who assists clinicians in practice transformation projects. [1][2][3][4][5][6][7][8] These facilitators commonly work toward improving the delivery of clinical interventions, particularly preventive services [9][10] ; facilitating research and quality improvement (QI) projects [11][12] ; and implementing health information technology.…”
mentioning
confidence: 99%
“…ORIGINAL ARTICLES I n health care literature, the term "practice facilitator" describes someone who assists clinicians in practice transformation projects. [1][2][3][4][5][6][7][8] These facilitators commonly work toward improving the delivery of clinical interventions, particularly preventive services [9][10] ; facilitating research and quality improvement (QI) projects [11][12] ; and implementing health information technology.…”
mentioning
confidence: 99%
“…This indicates that hospital leaders need to cultivate the right balance of conditions in order to sustain facilitation activities, and not rely on individual factors to drive the processes. Furthermore, these findings highlight the influence of group dynamics on implementation, an area often ignored in the empirical literature (Lessard et al, 2016).…”
Section: Overview Of Findingsmentioning
confidence: 78%
“…Furthermore, our post hoc analyses showed that continuity of team leadership also influenced sustainment patterns, where losing a team leader without finding a suitable replacement led to the remaining facilitators adopting a more defensive approach. These findings highlight the need to study change teams more closely (Lessard et al, 2016). Future studies can draw on the extensive team literature to examine the effects of factors such as team composition (Barrick et al, 1998) and shared mental models (Mohammed et al, 2010), which can help explain why some facilitator teams are effective while others are not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations